Analisis Komparatif Tingkat Kinerja Keuangan Bank Umum Syariah Dan Bank Umum Konvensional Di Indonesia ( Studi Kasus Pada Tahun 2015-2019 ) - Eka dian Kurnia santi; Widhian Hardiyanti SMB., MM (Universitas Sains dan Teknologi Komputer, 2021)
This study aims to test and analyze: (1) a comparative analysis of the level of performance of conventional commercial banks with Islamic commercial banks in 2015-2019, (2) the effect of the CAR, LDR / FDR, and NPL / NPF ratios partially or simultaneously on financial performance. in conventional commercial banks and Islamic commercial banks in 2015-2019. The population of this study is all published financial report data from Bank BNI and Bank BNI Syariah, Bank Mandiri and Bank Mandiri Syariah, Bank BRI and Bank BRI Syariah, Bank Bukopin and Bank Bukopin Syariah, Bank Mega and Bank Mega Syariah. The sample of the research is financial report data for 2015-2019. The process of collecting data is done by using documentation method in the form of published financial report data. The instrument test used was the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation. Data were tested using multiple linear regression, determinant test, F test (Goodness of Fit), and hypothesis testing using the t test. Based on the results of the study, it can be concluded as follows: (1) there is a significant difference in the level of financial performance of conventional commercial banks and Islamic commercial banks, this is evidenced by the results of the count test 3,724> t table 2,0086 and the probability of t count 0.001 <0.05: (2) Capital Adequacy Ratio has a positive and significant effect on financial performance at conventional commercial banks and Islamic commercial banks, this is evidenced by the t-count coefficient value of 3,724 <2,0086 and the probability of t count 0.325 <0.05; (3) Loan to Deposit Ratio has no effect on financial performance at conventional commercial banks and Islamic commercial banks, this is evidenced by the t value coefficient of 0.325 <2.0086 and the probability of t count 0.747> 0.05; (4) Non-Performing Loans have a significant negative effect on financial performance at conventional commercial banks and Islamic commercial banks, this is evidenced by the t-count coefficient value of -8.232> 2.0086 and the probability of t count 0,000> 0.05; (5) Capital adequacy ratio (CAR), loan to deposit ratio (LDR), and non performing loan (NPL) affect the financial performance of conventional commercial banks and Islamic commercial banks in 2015-2019, this is evidenced by the Fcount of 35,827 (> F table = 2.557) with a significance probability of 0.000 (<0.05). The results of the adjusted R2 test in this study obtained a value of 0.940. This shows that the financial performance is influenced by the capital adequacy ratio (CAR), loan to deposit ratio (LDR), non performing loan (NPL), amounting to 68.1%, while the remaining 31.9% is influenced by other factors not examined. in this research.